The portrait of Uganda's informal sector: What main obstacles do the sector face? - Salmon Mugoda; Stephen Esaku; Rose Kibuka Nakimu; Edward Bbaale (Cogent Economics & Finance, 2020)
In this paper, using primary data collected from business owners, we examine the nature and obstacles in the informal sector of Uganda. We find that education level matters in the selection of enterprises. The bulk of businesses, like eating kiosks, fish selling, shoe shining among others that require no specialized skill to operate were mainly run by primary school dropouts and those with no formal level of education. Furthermore, we find evidence of a strong entrepreneurial spirit among secondary school dropouts than at any other education level. Across all businesses surveyed, secondary school dropouts run a high number of informal enterprises. Evidence suggests that their motivation is driven by two key factors, namely, wanting to take advantage of an existing business opportunity and failure to find employment in the formal sector. The empirical results show that access to finance, crime, theft and disorder, electricity, water, taxes, burdensome inspections, and informal gifts are robust and significant obstacles to the operations of the informal sector in Uganda. Policies should focus on a regulatory framework that supports the sector to create secure livelihoods and generate employment opportunities for the unemployed rather than viewing the sector as a source of "illegality." Improving access to finance, providing regular power and water supply, and improving the tax regime would mitigate the obstacles faced by informal businesses leading to possible formalization. Informal sector businesses should not be perceived as "illegal entities" but rather complementary effort by an increasingly enterprising population in the country.
Keywords: D10; D13; E23; E26; H25; 330; business taxes; household production; informal economy; production; shadow economy; underground economy